ESTUDIO DE LAS ORGANIZACIONES DE LA ECONOMÍA POPULAR Y SOLIDARIA EN LA PARROQUIA EL CISNE DEL CANTON LOJA - Medina Vaca, Judith del Cisne (2018)
This work is part of the project called "Study of the forms of cooperation and solidarity that coexist in the framework of the Popular and Solidarity Economy in the rural parishes of the Loja Canton" that is developed in the Banking and Finance Career; aims to provide a solution to a problem affecting the rural sector of the Cisne parish, considering the study of organizations and the contribution of the Popular and Solidarity Economy in this area, in order to identify what would be the most appropriate way to potentiate it and with this, achieve economic and social development among its inhabitants. It began with the characterization of organizations in all aspects; at a productive, economic, social and financial level to know the reality in the Cisne parish; meeting 10 organizations such as: the association of truck cooperatives Sanctuary the Cisne; of Beekeepers; Snacks of candles; of people with disabilities; watering board; Committee of women entrepreneurs; Cisneña integration; and the Diocese of Loja. Through a workshop addressed to the representatives of the organizations, neighborhood presidents and community in general, it was possible to demonstrate that there is no intervention of financial organizations. A diagnosis was then made in order to identify the intervention of the Popular and Solidarity Economy entities in the study area. Finally, with the results obtained, a financial proposal was proposed with solidarity values and territorial relevance, for this it was necessary to use experiences developed in other parts of the country where groups of associations could overcome their shortcomings and progress continuously, identifying a viable alternative as is the work under associativity, based on the analysis of cases such as the "Salinerito", and the bibliography studied as a proposal was proposed a personalized associativity model according to the reality of the area. 5 This proposal has two components and is divided into activities in which a person in charge intervenes that will monitor the process and that in each phase will have the support of a professional team. Throughout this process they will be provided with the necessary tools to form an association and achieve sustainability that will be the generator of a social and economic change based on organized work and business vision on the part of the members of the organizations.